CFD simulation of forced convection heat transfer enhancement in pipe using Al2O3/water nanofluid - M. A. Elfaghia, Abdulhafid; A. Abosbaia, Alhadi; F. A. Alkbir, Munir; A. B. Omran, Abdoulhdi (Akademia Baru, 2022)
The advanced concepts of nano fluids offer an improvement in heat transfer compared to conventional heat transfer fluids. In recent years, researchers have been more attentive to the importance of higher thermal properties of nanofluids, especially in thermal conductivity and heat transfer. In this research, a numerical computational fluid dynamics (CFD) simulation is performed for forced convection heat transfer of Al2O3 nanofluids in a circular pipe with constant heat flow is carried out. The convective heat-transfer coefficient, Nusselt number, and friction factor of a nanofluid are studied as a function of Reynolds number and particle volume fraction. Volume fractions of 0.5, 1.0, and 2.0 percent of Al2O3 nanoparticles are studied, with range of Reynolds number of 6000 to 12000. The numerical results show that nanofluids have better convective heat performance than basic fluids, and the heat transfer improvement increases with the Reynolds number of the particles and volume concentration.